The Effectiveness of Inquiry-Based Learning on Reading Skills at SMAN I Lembang: Kurikulum Merdeka - Michelle Grace Stephanie Cahya; Caroline Victorine Katemba (JETAL: Journal of English Teaching & Applied Linguistic, 2023)
A curriculum is one of the learning instruments that educational institutions must be completed. Indonesian educational system has its new curriculum called Kurikulum Merdeka aims to respond the challenges of education, which in its realization must support skills in critical thinking, problem-solving, creativity, and innovation, as well as communication and collaboration skills for students. Inquiry-Based Learning is one of the methods that help students to think critically, innovative, and creatively. The method used in this research is a quantitative method using an experimental design with a control and experimental group and a pre-test and post-test design. It used a purposive sampling technique to determine the samples that involved 68 students: 34 students in the experimental class and 34 students in the control class. The data were gained through tests. Then, the data were analyzed through SPSS 21. The significant findings of the recent study were the roles of IBL is to improve the reading skills of tenth-grade students at SMAN 1 Lembang.